Overexpression of NtWRKY50 Increases Resistance to Ralstonia solanacearum and Alters Salicylic Acid and Jasmonic Acid Production in Tobacco - Liu, Qiuping; Liu, Ying; Tang, Yuanman; Chen, Juanni; Ding, Wei (Frontiers in Plant Science, 2017)
WRKY transcription factors (TFs) modulate plant responses to biotic and abiotic stresses. Here, we characterized a WRKY IIc TF, NtWRKY50, isolated from tobacco (Nicotiana tabacum) plants. The results showed that NtWRKY50 is a nuclear-localized protein and that its gene transcript is induced in tobacco when inoculated with the pathogenic bacterium Ralstonia solanacearum. Overexpression of NtWRKY50 enhanced bacterial resistance, which correlated with enhanced SA and JA/ET signaling genes. However, silencing of the NtWRKY50 gene had no obvious effects on plant disease resistance, implying functional redundancy of NtWRKY50 with other TFs. In addition, it was found that NtWRKY50 can be induced by various biotic or abiotic stresses, such as Potato virus Y, Rhizoctonia solani, Phytophthora parasitica, hydrogen peroxide, heat, cold, and wounding as well as the hormones salicylic acid (SA), jasmonic acid (JA), and ethylene (ET). Importantly, additional analysis suggests that NtWRKY50 overexpression markedly promotes SA levels but prevents pathogen-induced JA production. These data indicate that NtWRKY50 overexpression leads to altered SA and JA content, increased expression of defense-related genes and enhanced plant resistance to R. solanacearum. These probably due to increased activity of endogenous NtWRKY50 gene or could be gain-of-function phenotypes by altering the profile of genes affected by NtWRKY50.